Intravenous Administration of Human Amniotic Mesenchymal Stem Cells in the Subacute Phase of Cerebral Infarction in a Mouse Model Ameliorates Neurological Disturbance by Suppressing Blood Brain Barrier Disruption and Apoptosis via Immunomodulation. (17th June 2021) - Yoshida, Yasunori; Takagi, Toshinori; Kuramoto, Yoji; Tatebayashi, Kotaro; Shirakawa, Manabu; Yamahara, Kenichi; Doe, Nobutaka; Yoshimura, Shinichi
Neuro-inflammation plays a key role in the pathophysiology of brain infarction. Cell therapy offers a novel therapeutic option due to its effect on immunomodulatory effects. Amniotic stem cells, in particular, show promise owing to their low immunogenicity, tumorigenicity, and easy availability from amniotic membranes discarded following birth. We have successfully isolated and expanded human amniotic mesenchymal stem cells (hAMSCs). Herein, we evaluated the therapeutic effect of hAMSCs on neurological deficits after brain infarction as well as their immunomodulatory effects in a mouse model in order to understand their mechanisms of action. One day after permanent occlusion of the middle cerebral artery (MCAO), hAMSCs were intravenously administered. RT-qPCR for TNFα, iNOS, MMP2, and MMP9, immunofluorescence staining for iNOS and CD11b/c, and a TUNEL assay were performed 8 days following MCAO. An Evans Blue assay and behavioral tests were performed 2 days and several months following MCAO, respectively. The results suggest that the neurological deficits caused by cerebral infarction are improved in dose-dependent manner by the administration of hAMSCs. The mechanism appears to be through a reduction in disruption of the blood brain barrier and apoptosis in the peri-infarct region through the suppression of pro-inflammatory cytokines and the M2-to-M1 phenotype shift.